Potential impact of pore-scale incomplete mixing on biodegradation in aquifers: From batch experiment to field-scale modeling - Kang, Peter K.; Bresciani, Etienne; An, Seongnam; Lee, Seunghak (ELSEVIER SCI LTD, 2019)
Biogeochemical reactions take place when reactants are present at the same location and time, which occurs through pore-scale mixing. Although the degree of mixing should be variable in space and time, most conventional reactive transport models do not consider mixing-dependent reaction rates and often make predictions based on rates measured with batch experiments. We quantify the effect of pore-scale mixing on the biodegradation rate of dissolved organic carbon (DOC) with sediment batch experiments, and study its potential impact on the field-scale fate and transport of DOC with numerical simulations. We collected sediment samples from an aquifer storage transfer and recovery (ASTR) field site located in Busan, South Korea, and conducted batch experiments to measure mixing-dependent biodegradation rates. Complete mixing conditions were realized by continuously shaking the batch, and diffusion-limited mixing conditions were realized by keeping the batch under static conditions. The two mixing conditions are most widely used conditions in batch experiments and they also represent the maximum and minimum degree of mixing. The different mixing conditions led to significant differences in the biodegradation rates (a factor of 4.9 on average). We then performed reactive transport modeling using the measured biodegradation rates to study the potential impact of pore-scale incomplete mixing on the field-scale DOC biodegradation. The results show that pore-scale mixing can significantly affect the effectiveness of biodegradation at the ASTR site. We generalize this finding by performing a comprehensive nondimensional sensitivity analysis of the fate and transport of DOC to pore-scale mixing conditions over a wide range of Peclet and Damkohler numbers. We show that pore-scale incomplete mixing can be a major source of uncertainty in field-scale model predictions.
Keywords: DISSOLVED ORGANIC-MATTER; REACTIVE TRANSPORT; POROUS-MEDIA; NATURAL ATTENUATION; SILICATE MINERALS; DISSOLUTION RATES; RESIDENCE TIME; TRANSFORMATION; DISPERSION; MOBILITY